Catalyzed asymmetric hydrolysis of fluorinated chiral esters in locust haemolymph. In vitro19F NMR monitoring. Issue 2 (1997) - Menguy Menguy, L. L.; Hamm Hamm, S. S.; Cherton Cherton, J. C. J. C.
Abstract : 19 F NMR is used for monitoring the In vitro behaviour in locust organs or tissues of an ester with a fluorinated alkoxy structure and a chiral acyl moiety. In carrying out analysis directly in the biological media, the problematic extraction of polar metabolites is avoided, contributing to an easier and more reliable monitoring. Thus, in diluted haemolymph a remarkable enantioselectivity of the transformation is evidenced. Over a four hour period the ester R remains unalterated, while the S enantiomer is completely hydrolyzed. This enantioselectivity is the reverse of the trend which is generally observed in the hydrolysis of esters by lipases.